(untitled) (CIPEEX, 2025)
Vision and proprioception are fundamental for sensorimotor integration. Objectives: this study aims to identify the effects of a single session of transcranial direct current stimulation associated with proprioceptive exercises on the static balance of a 10-year-old child with moderate visual impairment. Methods: the work is a case report involving a 10-year-old child with moderate visual impairment. The patient was referred by professionals from the CEMAD of the municipality of Anápolis, GO. The therapeutic intervention consisted of using tDCS during a single session, associated with a series of static proprioceptive exercises. Results: The results obtained by comparing the postural balance parameters in the tests with eyes open (OASE) and eyes closed (OFSE) before and after the intervention show that postural stability was significantly affected in the tests with eyes open. The increase in the longitudinal displacement of the center of pressure (COP) suggests a decrease in stability, possibly due to a greater dependence on vision. The reduction in the number of peaks and in the amplitude of movements may indicate an attempt by the system to stabilize itself with less variability. Conclusion: These findings may guide future investigations into the mechanisms of postural balance adaptation under different sensory conditions.